2017
DOI: 10.1007/s11882-017-0753-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors in Preschool Children for Predicting Asthma During the Preschool Age and the Early School Age: a Systematic Review and Meta-Analysis

Abstract: A total of 17 studies were included in the analysis. Factors associated with developing asthma in children ≤ 10 years of age (both pre-school and early school age) included male gender (pooled OR = 1.70, P < 0.001), atopic dermatitis (pooled OR = 2.02, P < 0.001), a family history of asthma (pooled OR = 2.20, P < 0.001), and serum IgE levels ≥ 60 kU/l or having specific IgE (pooled OR = 2.36, P < 0.001). A history of exposure to smoke or wheezing was also associated with persistent asthma in early school age (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 30 publications
3
55
0
3
Order By: Relevance
“…The other important risk factors for asthma, that have been previously described, included parental history of allergic disease(46), a child's atopy status and concomitant other allergic disease (47). The strength of this study was to demonstrate that having a combination of any two of these known risk factors for asthma had an additive effect of asthma risk, and that this risk also increased in relation to area of residence in early life, with an increasing rural-town-city gradient.…”
Section: Discussionmentioning
confidence: 99%
“…The other important risk factors for asthma, that have been previously described, included parental history of allergic disease(46), a child's atopy status and concomitant other allergic disease (47). The strength of this study was to demonstrate that having a combination of any two of these known risk factors for asthma had an additive effect of asthma risk, and that this risk also increased in relation to area of residence in early life, with an increasing rural-town-city gradient.…”
Section: Discussionmentioning
confidence: 99%
“…See Table . These are well‐established predictors of asthma suggesting that children identified by the OASIS algorithm and not by parent‐reported asthma may represent future asthma cases (ie, those who have not yet received a formal diagnosis by their primary care physician). A statistically significant factor associated with asthma identified by parent‐report but not OASIS was male sex (aOR: 0.86; 95% CI: 0.77‐0.96).…”
Section: Resultsmentioning
confidence: 99%
“…Children who have a family history of allergies or family history of asthma were more likely to be diagnosed with asthma compared to children who do not have these risk factors . These well‐established predictors of asthma suggest that children identified by the OASIS algorithm and not by parent‐reported asthma may represent children who utilized health services similar to children diagnosed with asthma but were not yet formally diagnosed by their primary care physician (ie, future asthma cases). The original OASIS algorithm validation study in children also found a relatively high number of cases (84/630) coded as asthma based on the administrative data but assigned a non‐asthma diagnosis based on the review of the clinical record .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Asthma has become one of the most common chronic medical conditions and about 300 million people globally are estimated to suffer from asthma [1][2][3]. Asthma is also regarded as the most common chronic disorder in children [4,5]. This disease can result in considerable morbidity and remarkably reduced quality of life in paediatric populations, and hospitalizations and urgent medical care is sometimes required for these patients [6,7].…”
Section: Introductionmentioning
confidence: 99%